Channel Assignment Strategy Based on the Sustained-Transmission Rule of Nodes in Cognitive Radio Sensor Network - Xinbin Li; Zequn Huang; Song Han; Jianmei Chen (Dianxin kexue)
In order to improve the success rate of data packet transmission in heterogeneous and hierarchical cognitive radio sensor network,the nodes were divided into sustained-transmission and non-sustained-transmission conditions.The ways of improving the success rate of data packet transmission are more energy consumption and better channel assignment,so that there is a type of centralized channel assignment strategies.At the same time,in order to reduce the energy consumption per bit in information transmission process of nodes,the packet size adaptation mechanism was optimized,ensuring the optimal packet size of non-sustained-transmission nodes.Simulation results demonstrate that the channel assignment strategy and the optimization mechanism improve the efficiency of energy utilization and the performance of network.